Analisis Potensi Pajak Parkir dalam Meningkatkan Penerimaan Pajak Daerah di Kabupaten Bekasi - Dwikora Harjo; Iwan Irwansyah; Sri Widah Sari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The background of this research is the low level of realization of parking tax revenue in Bekasi Regency. This is a problem because the parking tax target and realization should increase from year to year. This study aims to provide a clear picture of the potential for parking tax revenues in Bekasi Regency.The type of research used is descriptive qualitative research with survey method. Data was collected through observation, interviews and documentation. The data obtained was then analyzed qualitatively by organizing the data, breaking it down into units, compiling it into patterns, describing it into words and sentences, and drawing conclusions. The Bekasi Regency Regional Revenue Agency has managed parking to increase regional tax sector revenues with several activities, including providing guidance, strengthening the collection process, increasing administrative efficiency, coordinating with related agencies and holding campaigns. However, the results of the study indicate that the realization of the parking tax has not optimal. The potential for parking taxes in Bekasi Regency is still very high whivh has not been explored by the government, because in its implementation there are still obstacles, so that efforts need to be made by the Bekasi Regency Regional Revenue Agency to increase parking tax revenues.